2006
DOI: 10.1158/0008-5472.can-05-4268
|View full text |Cite
|
Sign up to set email alerts
|

β-Catenin/Wnt Signaling Regulates Expression of the Membrane Type 3 Matrix Metalloproteinase in Gastric Cancer

Abstract: Activation of Wnt signaling through B-catenin dysregulation occurs in numerous human tumors, including gastric cancer. The specific consequences of Wnt signaling in gastric cancer, however, are not well characterized. This study shows that the introduction of mutant B-catenin into gastric cancer cell lines by adenoviral infection enhances invasiveness and proliferation and up-regulates the expression of the gene encoding the matrix metalloproteinase (MMP) family member membrane type 3 MMP (MT3-MMP). Up-regulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
90
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(95 citation statements)
references
References 25 publications
2
90
0
Order By: Relevance
“…These results suggest that EMMPRIN-mediated regulation of b-catenin signaling is independent of MMP regulation and perhaps MMP expression is downstream of the Wnt/b-catenin signaling pathway. However, we cannot exclude the possibility that b-catenin signaling and MMP induction are stimulated independently through two distinct and separate pathways, although there is evidence that MMP expression can be stimulated by Wnt signaling (Roth et al, 2000;Soon et al, 2003;Lowy et al, 2006).…”
Section: Discussionmentioning
confidence: 95%
“…These results suggest that EMMPRIN-mediated regulation of b-catenin signaling is independent of MMP regulation and perhaps MMP expression is downstream of the Wnt/b-catenin signaling pathway. However, we cannot exclude the possibility that b-catenin signaling and MMP induction are stimulated independently through two distinct and separate pathways, although there is evidence that MMP expression can be stimulated by Wnt signaling (Roth et al, 2000;Soon et al, 2003;Lowy et al, 2006).…”
Section: Discussionmentioning
confidence: 95%
“…On the other hand, nuclear b-catenin is correlated with an invasive phenotype in intestinal-type tumors [198] . This increase in tumor invasion is likely mediated by the upregulation of Wnt transcriptional targets, such as EphA2 (erythropoietin-producing hepatocellular) and membrane type 3 matrix metalloproteinase (MT3-MMP) genes [199,200] . Furthermore, evidence provided by Kim et al [201,202] suggests that TC1 (C8orf4), which is upregulated in high-grade gastric cancers, coordinates the upregulation of Wnt/b-catenin target genes involved in the aggressive biological behavior and poor clinical outcome observed in advanced gastric cancer [202,203] .…”
Section: Wnt/b-catenin Signaling and Metastatic Potential In Gastric mentioning
confidence: 99%
“…Once the degradation of h-catenin is repressed (e.g., inhibition of GSK3h kinase activity), h-catenin accumulation results in its translocation into the nucleus and interaction with Tcf/LEF family transcription factors to activate the expression of target genes important for cell proliferation, such as c-myc and cyclin D1 (28). The h-catenin -dependent oncogenic signaling network is involved in the multistep process of tumorigenesis, including cell proliferation (29), invasion (30), and inhibition of apoptosis (31). The results in our study showed that the inhibition of CacyBP/SIP protein increased the expression of h-catenin without a change in the mRNA level in gastric cancer cells, suggesting that CacyBP/SIP may be a critical component required in the h-catenin ubiquitin-degradation pathway.…”
Section: The Expression Of B-catenin In Transfectantsmentioning
confidence: 99%